2022
DOI: 10.1002/ajh.26778
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of anemia response to momelotinib therapy in myelofibrosis and impact on survival

Abstract: We retrospectively reviewed 72 anemic patients with myelofibrosis (MF; median age 68 years), who were JAK2 inhibitor‐naïve at the time of study entry to a phase‐1/2 momelotinib clinical trial. Driver mutation profile included JAK2 69%, CALR 17%, MPL 8%, and triple‐negative 6%; other mutations included ASXL1 39% and SRSF2 17%. Momelotinib was administered at a median dose of 300 mg daily. Anemia response was assessed by formal criteria and documented in 44% of all patients with hemoglobin levels below the sex‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 29 publications
(78 reference statements)
3
31
0
Order By: Relevance
“…Momelotinib and pacritinib have been shown to manifest erythropoietic activity, in addition to their favorable effect on splenomegaly and constitutional symptoms. Momelotinib is currently not FDA‐approved but its value in improving anemia in patients with MF has been documented in both phase‐2 and phase‐3 studies 54,91,92 . In a recently updated analysis of 72 Mayo Clinic patients with MF who were JAKi‐naïve and anemic prior to treatment with momelotinib, 54 44% experienced anemia response with median response duration of ⁓20 months; predictors of anemia response included post‐ET MF (83% vs. 37%) and serum ferritin level <55 mcg/L (89% vs. 38%).…”
Section: Symptom‐directed Therapymentioning
confidence: 99%
“…Momelotinib and pacritinib have been shown to manifest erythropoietic activity, in addition to their favorable effect on splenomegaly and constitutional symptoms. Momelotinib is currently not FDA‐approved but its value in improving anemia in patients with MF has been documented in both phase‐2 and phase‐3 studies 54,91,92 . In a recently updated analysis of 72 Mayo Clinic patients with MF who were JAKi‐naïve and anemic prior to treatment with momelotinib, 54 44% experienced anemia response with median response duration of ⁓20 months; predictors of anemia response included post‐ET MF (83% vs. 37%) and serum ferritin level <55 mcg/L (89% vs. 38%).…”
Section: Symptom‐directed Therapymentioning
confidence: 99%
“…Among 28 patients who were transfusion-dependent at baseline, resolution of transfusion need was documented in 13 (46%) patients and the response lasted for a median of 20.3 months (range 4-61.3); independent predictors of response in this group of patients included intermediate-vs high-risk disease (100% vs 0%), serum ferritin level <833 mcg/L (80% vs 28%), and post-ET vs primary/post-PV MF (80% vs 39%). 59 Among all 72 study patients, treatment was discontinued in 93% after median treatment duration of 20 months. Post-momelotinib median survival was 3.2 years with 5 and 10-year survival rates at 31% and 19%, respectively.…”
Section: The Original Mayo Clinic-centered Phase-1/2 Clinical Trialmentioning
confidence: 99%
“…The high treatment discontinuation rates attest to the transient benefit from JAKi therapy and although short-term survival was superior in spleen and anemia responders, long-term survival was not impacted by neither achievement of spleen nor anemia response with 10-year survival rates of <25%. Moreover, we have recently shown that the short-term survival benefit associated with anemia response in momelotinib treated MF patients might be limited to those with unfavorable genetic profile [21]. It is to be noted that patients remained on momelotinib longer and had higher anemia response rates compared to ruxolitinib, despite which survival was similar, which is likely due to momelotinib treated patients being older and belonging to higher DIPSS-plus risk.…”
Section: Discussionmentioning
confidence: 97%